Deconstructing Growth - A Business Cycle Accounting Approach with application to BRICs - Suparna Chakraborty; Keisuke Otsu (University of Kent, School of Economics, 2012)
What are the economic mechanisms that account for sudden growth spurts? Are these mechanisms similar across episodes? Focusing on the economic resurgence of the BRICs over the last decade, we employ the Business Cycle Accounting methodology developed by Chari, Kehoe and McGrattan (2007) to address these questions. Our results highlight that while efficiency wedges do contribute in a large part to growth, especially in Brazil and Russia, there is an increasing importance of investment wedge especially in the late 2000s, noted in China and India. The results are typically related to the stages of development with Brazil and Russia coming off a crisis to grow in the 2000s, while India and China were already on a stable growth path. Our conclusions are robust to alternative methodological extensions where we allow shocks to the trend component of efficiency as opposed to traditional shocks to the cyclical component, as well as to standard modifications where we allow for investment adjustment costs. Relating improvements in wedges to institutional and financial reforms, we find that financial development and improvements in effective governance in BRICs are consistent with improvements in investment and efficiency wedges that led to growth.
Keywords: E32; E33; 330; BRIC; business cycle accounting; efficiency; market frictions; trend shocks; investment adjustment costs